Peritonitis: Culprit for peritoneal dialysis decline - Kumar, Kishore; Kumar, Jais; Naureen, Chaudhri (Journal of Clinical Nephrology, 2019)
Peritonitis is the main complication of peritoneal dialysis caused the withdrawal of treatment like peritoneal dialysis which was used as primary treatment modality few years back in Pakistan. With this motto to know the exact cause of peritonitis this retrospective study was done and 35 out of 42 pervious peritoneal dialysis patients who had peritonitis were analyzed using old data. A total of 57 bags of all these peritonitis patients were analyzed in department of microbiology during the year 2007-2011. Out of these bags positive culture was obtained from 42 bags (74%). Most of patients with positive culture were undergoing acute peritoneal dialysis 66.67% and rest were on chronic ambulatory peritoneal dialysis. Main concern was the yield of organisms causing culture positive peritonitis. It was found that bacterial peritonitis was positive in 80%, fungal peritonitis was 11% and mycobacterium tuberculosis peritonitis was 09%. Various culture techniques along with Gram Stain, Zeihl Nielsen Stain and Auramine stain were used for knowing the yield. Limitations: Old and only small available data of peritonitis patients and stop of further peritoneal dialysis.